The effect of celecoxib and its combination with imatinib on human HT-29 colorectal cancer cells: Involvement of COX-2, Caspase-3, VEGF and NF-ÎºB genes expression - Atari-Hajipirloo, S; Nikanfar, S; Heydari, A; Noori, F; Kheradmand, F (Cellular and Molecular Biology, 2016)
It has been shown that combination of imatinib (IM) with other agents may have some advantages in avoiding toxicity and resistance caused by this drug. The selective cyclooxygenase-2 inhibitor, celecoxib (CX), has been known to have antitumor and chemo-sensitizing effect in the treatment of colorectal cancer. In this study, we investigated the effectiveness of CX and its combination with anticancer agent IM on human colorectal cancer HT-29 cell and their probable molecular targets. Cultured HT-29 cells were exposed to IC50 dose of CX, IM, and their combination (half dose of IC50) for 24 hours to assess their effect on proliferation inhibition by MTT assay. The caspase-3 activity was estimated in HT-29 cells with colorimetric kit. COX-2, Caspase-3, VEGF and NF-ÎºB genes expression was also investigated using real-time PCR method. Combined treatment with IM and CX, resulted in a significant (PË‚0.05) decrease in cell viability and increased caspase-3 enzyme activity. Decreased COX-2 gene expression has been found in CX and combined treated group. Significant increase in Caspase-3 gene expression has been shown in IM and combined treated cells. In conclusion, the present in vitro study with colon cancer cell line demonstrated that CX and its combination with IM improved the anticancer activity of each component. Caspase-3 and COX-2 dependent molecular targets seem to be involved in mediating the anti-proliferative effects of IM and CX combination. Of course, the other molecular pathways are also likely to play the role and should be explored in future studies.